2002
DOI: 10.1292/jvms.64.1123
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Survey of Bovine Abortion in Korea: With Special Emphasis on Neospora caninum.

Abstract: ABSTRACT. Causes of bovine abortion were surveyed in Korea within a designated period from the cases submitted to the Department of Veterinary Pathology, College of Veterinary Medicine, Seoul National University. One hundred and eighty aborted fetuses and mat ernal sera were evaluated by necropsy, histopathology, bacteriology, virology, PCR, and serologic tests. The causes of abortion were identified in 108 (60%) cases, of which 38 (21.1%) were due to the infection with Neospora caninum. None of the 38 cases s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
18
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 15 publications
(17 reference statements)
6
18
5
Order By: Relevance
“…Despite our finding of low prevalence of N. caninum in native Korean goats, these results are worth noting because N. caninum infection in cattle has been associated with a high proportion of abortions (25.0%; 45/180) in Korea (Kim et al 2002). The seroprevalence of N. caninum in dogs in Korea has been reported at 10.3% (35/340) and specifically in rural dogs at 21.6% (11/51) (Kim et al 2003).…”
Section: Discussioncontrasting
confidence: 61%
“…Despite our finding of low prevalence of N. caninum in native Korean goats, these results are worth noting because N. caninum infection in cattle has been associated with a high proportion of abortions (25.0%; 45/180) in Korea (Kim et al 2002). The seroprevalence of N. caninum in dogs in Korea has been reported at 10.3% (35/340) and specifically in rural dogs at 21.6% (11/51) (Kim et al 2003).…”
Section: Discussioncontrasting
confidence: 61%
“…Neosporosis has been reported in many countries (Kim et al, 2002;Kim et al, 1998;Gondim et al, 2004) with different prevalence rates since the disease was recognized in 1988. The seroprevalence of antibody to N. caninum in this study is 4.84%, in dairy cattle of western dairy pocket area in Chitwan, is lower than that reported for cattle in Brazil (14.09%) (Gondim et al, 2004), Romania (34.6%) (Gvavrea et al, 2011), Pakistan (43%) (Nazir et al, 2013), Jordan (35 %) (Talafha and Al-Majali, 2013), China (15.07%) (Xu et al, 2012), India (12.61%) (Sengupta et al, 2012), Iran (10.5%) (Nematollahi et al, 2011), Sudan (10.7%) (Ibrahim et al, 2012) but resembles that reported in Australia (3.2%) (Nasir et al, 2012), Korea (4.1%) (Kim et al, 2002), Czech Republic (5.83%) (Vaclavek et al, 2003), France (5.6%) (Ould et al, 1999) and Japan (5.7%) (Koiwai et al, 2006). This difference in seroprevalence may be due to the type of test used, their cut-off points, change in geographic area, variation in sample size and other associated risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…populations world-wide (Kim et al, 2002). The diagnosis of abortions often presents a challenge to the farm owner and the veterinarian in charge.…”
Section: Diagnosis Of Abortionmentioning
confidence: 99%